2021
DOI: 10.1177/10547738211041692
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of an Online-Self-Management Program for Rheumatoid Arthritis

Abstract: This qualitative descriptive study aimed to explore expectations of patients and healthcare experts for an online self-management program for rheumatoid arthritis. Participants were recruited from rheumatology clinics, medical centers, and universities in Taiwan. Individual face-to-face, semi-structured interviews were conducted with patients ( n = 16) and healthcare experts ( n = 7). Content analysis of the interview data resulted in five subthemes for expectations of an online self-management program: inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This highlights the need for exible interventions in clinical practice. Other studies have found that, e.g., online self-management support can be useful (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for exible interventions in clinical practice. Other studies have found that, e.g., online self-management support can be useful (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…The program was based on two qualitative studies, which explored patient needs and recommendations for self-management of rheumatoid arthritis ( Chen, Yu, Kao, & Shao, 2022 ; Chen, Yu, Lee, & Shao, 2022 ). The study was to be conducted as a two-arm exploratory RCT with an intervention and control group with data collected at enrollment (baseline) and a follow-up at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Taiwanese patients who believe their lives are controlled by God or fate often adopt strategies to achieve peace of mind instead of attempting to draw on personal resources that will allow them to be take responsibility for staying healthy [40]. The belief that health is a matter of faith has been shown to inhibit patients from adopting healthy behaviors by shifting responsibility for their chronic disease to God or fate [45,46]. Religious beliefs of Buddhism and Taoism could reduce self-efficacy for patients with RA in Taiwan because they do not believe they are able or have the responsibility to change their health condition.…”
Section: Austin Publishing Groupmentioning
confidence: 99%